Governance and digital transformation in schools with 1:1 tablet coverage - Tømte, Cathrine E.; Smedsrud, Jørgen Hammer (Frontiers in Education, 2023)
There is an increasing trend of 1:1 coverage of tablets in schools in Scandinavia. Several studies have reported on pedagogical possibilities and challenges, but less is reported about how this change is perceived and practised by other stakeholders. We interviewed public school owners and leaders in Norway and found school owners used various models to support their schools, and school leaders held varied views on their roles in promoting the implementing 1:1 coverage in schools. Considering these findings, we discuss whether establishing overall national guidelines might help school owners and school leaders to effect digital transformation in schools and whether such guidelines would support or counteract school leaders' autonomy and ability to adapt the digital transformation to their local context.